METHODICAL BASES OF ESTIMATION GLOMERULAR FILTRATION RATE IN UROLOGICAL PRACTICE - M. M. Batiushin (Вестник урологии, 2017)
The article presents a review of methodological issues of estimation of glomerular filtration rate in urologic practice. Author examine the current international and national recommendations, in particular by KDIGO, the recommendations of the scientific society of nephrologists of Russia, Association of urologists of Russia, the results of comparative analysis of different methods of assessing glomerular filtration rate. It is shown that the currently calculated methods of assessment of glomerular filtration rate have advantages over technique of clearance. The advantages and disadvantages of methods for calculating glomerular filtration rate by the formula of Cockcroft-Gault and MDRD. The author lists the pathological conditions in urological practice, in which there is a need to assess glomerular filtration rate, given nomograms and links to online calculators for quick and easy calculation of glomerular filtration rate.